Efficacy of DNA hypomethylating capacities of 5-aza-2'-deoxycytidine and its alpha anomer - Fojtova, Miloslava; Piskala, Alois; Votruba, Ivan; Otmar, Miroslav; Bartova, Eva; Kovarik, Ales (Pharmacological research, 2007)
In this paper, we have compared hypomethylating ability of classical beta-d-anomer of 5-aza-2'-deoxycytidine (5-aza-CdRf) and its alpha anomer in cell cultures. Alpha anomers of nucleosides generally exhibit low biological activity compared to their beta counterparts. It is reported that alpha anomer of 5-aza-CdRf efficiently hypomethylated genomic DNA in human T-lymphoblastoid CCRF-CEM cells. Satellite 2 and 18S rDNA were hypomethylated by alpha anomer at concentrations comparable to the beta form. However, the toxicity of the alpha anomer was 4-fold less than that of beta form. Contrast to CCRF-CEM the A549 lung carcinoma cells, possessing negligible level of methylation at repetitive loci, were highly resistant to 5-aza-CdRf treatment suggesting that global genomic methylation might be needed to mediate cytotoxic effect of the drug. Possible mechanisms of inhibition of DNA methylation by alpha anomer are discussed. In conclusion, alpha anomer of 5-aza-CdRf displaying lower host cytotoxicity than the classical beta form may be of potential use in epigenetic therapy.
Keywords: Blotting, Southern; azacytidin; Humans; decitabin; Decitabine; Blotting, Western; lidé; apoptóza; DNA Methylation; metylace DNA; Isomerism; DNA Probes; antimetabolity; nádorové buněčné linie; Southernův blotting; Azacitidine; Cell Line, Tumor; Antimetabolites; western blotting; isomerie; Apoptosis; DNA sondy